The Effect of Combining Isometric Handgrip Exercise with Sundanese Degung Instrumental Music on Blood Pressure Changes in Elderly People with Hypertension - Sopiani, Riscka; Jamiat, Nandang; Sajodin, Sajodin (Universitas Muhammadiyah Surakarta, 2024)
Hypertension is defined as a condition that blood pressure is more than 140/90 mmHg. Because the aging process causes blood vessels to stiffen and the elasticity of the ventricular walls to decrease, the elderly are categorized as a health susceptible category. This disorder can lead to hypertension, which can have catastrophic effects such as stroke and even death. The purpose of this study was to determine isometric handgrip exercise (IHE) therapy accompanied by degung instrumental music affects blood pressure changes in elderly people with hypertension. A quantitative design with a quasi-experimental approach, pretest and post-test methodologies, and a control group was used for the study. The sample strategy employed in this study will be non-probability sampling (purposive sampling). 59 samples were collected and divided into intervention and control groups. This study lasted 2 × 2 minutes, was interrupted by 3 minutes of rest, and was conducted on three consecutive days. The result of study showhed that the Sig (2-tailed) value was 0.00, indicating that there is an influence between the Isometric Handgrip Exercise intervention accompanied by Sundanese degung instrumental music on blood pressure changes in elderly people with hypertension. The IHE intervention accompanied by Sundanese degung instrumental music is recommended as IHE in decreasing blood pressure in hypertension patients